ANALISIS PENGENDALIAN INTERNAL PENCAIRAN PIUTANG DI PT VICTORY CIPTA MAKMUR CABANG SUKAHATI - ., Muhlis; Riskya, Anita (Economicus, 2021)
The marketing strategy helps the company maintain its market share by using a credit sales policy so that accounts receivable arise which often experience problems in terms of disbursing units from leasing. This study uses a qualitative method with a descriptive approach because this research is not clear and there is no suitable data about the problem being studied. This research was conducted directly at PT Victory Cipta Makmur Sukahati Branch. The purpose of this study was to determine the constraints on disbursement of repayments through the Brainstorming method, then the results of the causes of these problems were searched based on the data and facts available at PT Victory Cipta Makmur Sukahati Branch, then an analysis was carried out using the Seven Tools For Quality Control analysis tool, in which this research using 3 analyzes,namely checksheets,Pareto diagrams,and fishbone diagrams. From the results of the study, it was concluded that internal control was less effective as seen from the final results of the fishbone diagram which explained the human factor in carrying out the billing process that was not in accordance with the company's SOP. There are suggestions for good corrective actions to control in the form of further checking on billing.